Emergence and clonal spread of colistin resistance due to multiple mutational mechanisms in carbapenemase-producing Klebsiella pneumoniae in London. Issue 1 (December 2017) - Otter, Jonathan; Doumith, Michel; Davies, Frances; Mookerjee, Siddharth; Dyakova, Eleonora; Gilchrist, Mark; Brannigan, Eimear; Bamford, Kathleen; Galletly, Tracey; Donaldson, Hugo; Aanensen, David; Ellington, Matthew; et al.
Abstract Carbapenemase-producing Enterobacteriaceae (CPE) are emerging worldwide, limiting therapeutic options. Mutational and plasmid-mediated mechanisms of colistin resistance have both been reported. The emergence and clonal spread of colistin resistance was analysed in 40 epidemiologically-related NDM-1 carbapenemase producingKlebsiella pneumoniae isolates identified during an outbreak in a group of London hospitals. Isolates from July 2014 to October 2015 were tested for colistin susceptibility using agar dilution, and characterised by whole genome sequencing (WGS). Colistin resistance was detected in 25/38 (65.8%) cases for which colistin susceptibility was tested. WGS found that three potential mechanisms of colistin resistance had emerged separately, two due to different mutations inmgrB, and one due to a mutation inphoQ, with onward transmission of two distinct colistin-resistant variants, resulting in two sub-clones associated with transmission at separate hospitals. A high rate of colistin resistance (66%) emerged over a 10 month period. WGS demonstrated that mutational colistin resistance emerged three times during the outbreak, with transmission of two colistin-resistant variants.